The Influence of Sport Representation and Attitudes Toward Strength Training on Neuromuscular Performance Profiles in University Athletes: Part II Male Athletes. - McClean, Zachary J.; da Silva Torres, Ricardo; Herzog, Walter; Pasanen, Kati; Lun, Victor; Jordan, Matthew J. (Journal of Strength & Conditioning Research, 2026)
McClean, ZJ, da Silva Torres, R, Herzog, W, Pasanen, K, Lun, V, and Jordan, MJ. The influence of sport representation and attitudes toward strength training on neuromuscular performance profiles in university athletes: Part I—Male athletes. J Strength Cond Res 40(3): 324–336, 2026—Strength, power, and plyometric testing are essential to evaluate neuromuscular performance in athletes. However, this approach creates datasets with numerous outcome measures that can lead to challenges for interpretation and establishing relevant performance benchmarks for preseason testing and performance-readiness after injury. The idea that athlete performance profiles exist within a larger population has been suggested, but limited research has explored this concept or suggested methodologies for delineating relevant profiles. Exploring the existence of neuromuscular performance profiles in university athletes while accounting for the influence of the sport environment and psychosocial factors, such as attitudes toward strength training, may support more athlete-specific neuromuscular benchmarks. Healthy male university athletes (n = 272) from 5 sports completed a comprehensive neuromuscular performance testing battery and a questionnaire that included assessment of attitudes toward strength training. Unsupervised machine learning applied to the body weight–normalized neuromuscular performance dataset, along with Fisher's exact tests, was used to examine differences in attitudes toward strength training across clusters (alpha = 0.05). Five profiles were identified, including a high strength/high power/braking-dominant jump strategy cluster with a large ice hockey representation and a high strength/high power/fast jump strategy cluster consisting mostly of field-sport athletes. Differences in attitudes toward training were noted across profiles (p < 0.05); for instance, athletes in a low-strength/low-power profile tended to prefer training in a more private training environment (p = 0.023). These results may help inform neuromuscular performance benchmarks in male university athletes, while the psychosocial characteristics of these profiles may provide insight into increasing strength training engagement in this population.